Influence voltage asymmetry transition asynchronous electric shock loads in - Savchenko, V.; Sinyavsky, O.; Savchenko, V. (Energy and Automation, 2015)
The research of electromagnetic and electromechanical transients in asynchronous electric asymmetry in voltages. The influence of voltage unbalance of the length of the transition process and the established rate.